Some Families of Two-Step Simultaneous Methods for Determining Zeros of Nonlinear Equations. (13th April 2011) - Mir, Nazir Ahmad; Muneer, Rifka; Jabeen, Iffat
Abstract : We construct two families of two-step simultaneous methods, one of order four and the other of order six, for determining all the distinct zeros of single variable nonlinear equations. The convergence analysis of both the families of methods and the numerical results are also given in order to demonstrate the efficiency and the performance of the new iterative simultaneous methods.